2005
DOI: 10.1021/ie049225z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pervaporation and Vapor Permeation Hybrid Distillation Processes

Abstract: Previous studies have shown that hybrid distillation processes using either pervaporation or vapor permeation can be very attractive for the separation of mixtures. In this paper, a comparison between these two hybrid processes has been made. A tool has been presented that can assist designers and engineers to decide which process is more convenient for a specific application. Water removal from acetonitrile has been used as an example. A hybrid process with vapor permeation is preferred when the membrane is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
(37 reference statements)
0
34
0
Order By: Relevance
“…However, the capital cost of pervaporation processes can be higher than distillation. M a n u s c r i p t Hybrid membrane-distillation processes can potentially exploit the advantages of distillation and pervaporation, while overcoming the disadvantages of both 5,7 . A conventional pervaporation-distillation hybrid system (ECPDS) consists of a distillation column and an externally connected pervaporation module 1,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the capital cost of pervaporation processes can be higher than distillation. M a n u s c r i p t Hybrid membrane-distillation processes can potentially exploit the advantages of distillation and pervaporation, while overcoming the disadvantages of both 5,7 . A conventional pervaporation-distillation hybrid system (ECPDS) consists of a distillation column and an externally connected pervaporation module 1,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, it can be used as a final treatment stage. Applications for binary mixtures 7,9,10 and multicomponent mixtures 11,12 can be found in literature, where the effect of the membrane properties and operating variables on the hybrid process performance have been discussed. It has been shown that a retentate stream composed of a mixture of liquid and vapour can reduce the membrane area requirements compared to conventional pervaporation units and membrane savings higher than 40 % can be achieved 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, very high selectivities are not necessarily required for hybrid distillation and vapor permeation systems. More results regarding this analysis can be found elsewhere (Fahmy et al, 2001;Fontalvo et al, 2005). …”
Section: Feed Tray 20mentioning
confidence: 98%
“…Some years ago, Fontalvo et al (Fontalvo et al, 2005) presented simulation results of a hybrid distillation-membrane process using an integrated system of Matlab within the Aspen Plus interface. In this publication, the specific details for this connection were not shown.…”
Section: Introductionmentioning
confidence: 99%
“…It also leads to lower operating and investment costs. Fontalvo [102] showed that total cost reductions of up to 60% are possible using a hybrid membrane distillation process for acetonitrile dehydration.…”
Section: Integrated Distillation-pervaporation/vapour Permeation Systemsmentioning
confidence: 99%